2006
DOI: 10.1002/cncr.21745
|View full text |Cite
|
Sign up to set email alerts
|

Defining “Success” in recruitment of underrepresented populations to cancer clinical trials

Abstract: Although medically underserved groups bear a heavy burden of cancer disease and governmental agencies have required inclusion of minorities and women in cancer clinical trials since 1993, many of these groups are underrepresented in cancer prevention or treatment clinical trials. To assess and enhance recruitment of underrepresented populations into cancer-related clinical trials, investigators and governmental agencies need consistent measurement approaches for recruitment that can be applied to diverse setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
69
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 51 publications
0
69
0
Order By: Relevance
“…One of the most difficult aspects of the review was comparing recruitment strategies across studies that used different language, i.e., enrollment, recruitment, participant, registrant. Using consistent measurement approaches for underrepresented groups would greatly improve comparability of recruitment strategies across trials and may improve applicability of trial results to multiple populations [61].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most difficult aspects of the review was comparing recruitment strategies across studies that used different language, i.e., enrollment, recruitment, participant, registrant. Using consistent measurement approaches for underrepresented groups would greatly improve comparability of recruitment strategies across trials and may improve applicability of trial results to multiple populations [61].…”
Section: Discussionmentioning
confidence: 99%
“…It is critical that investigators develop a priori recruitment goals for patients Ն65 years of age when designing a therapeutic clinical trial. A framework for deciding upon a recruitment goal has been outlined by Bolen et al, which takes into consideration the current adequacy of care, burden of disease among groups, and the known biologic or cultural differences between groups [28]. It has been successfully demonstrated by Moinpour et al in a prostate cancer randomized controlled prevention trial that set an a priori recruitment goal for African American men based upon the national proportion of African American men in the age subset they were evaluating [29].…”
Section: Discussionmentioning
confidence: 99%
“…13,18 There is also a question of the methodologic rigor of trial enrollment studies, as prior work has suggested that studies of recruitment interventions vary in their definition of successful recruitment, and others have called for more complete reporting of racial, ethnic and cultural composition of subjects in trials as well as thorough descriptions of recruitment successes and failures. 13,21 We therefore conducted a systematic review to identify which minority recruitment strategies have been attempted and which ones are effective and efficient. We also assessed the methodologic rigor of these studies with regard to quantitative and qualitative data reporting and ability to draw inferences.…”
mentioning
confidence: 99%